Determinants of Compliance with Complication Prevention in Type 2 Diabetes Mellitus Patients in the Outpatient Unit of Tk. II Udayana Hospital - I Wayan Remiasa; I Gede Putu Darma Suyasa2; A.A. Ayu Yuliati Darmini; Sri Dewi Megayanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2022)
Introduction: Diabetes Mellitus (DM) is one of the main causes of 1.6 million deaths every year in the world. Irregularity of blood sugar control and the absence of a healthy lifestyle are risk factors and complications of type 2 Diabetes Mellitus (DM) patients. Many factors need to be studied related to compliance to diabetes complication prevention. Objective: The objective of this research was to analyze the determinants of compliance to complication prevention in type 2 DM patients. Method: This research used a correlation design with a cross-sectional approach. The sample was 233 type 2 DM patients recruited using the convenience sampling technique. Data were collected using questionnaires and analyzed using univariate, bivariate, and multivariate analyses. Results: The results of the Chi-Square analysis showed several factors had a significant relationship with compliance with diabetes complication prevention, including knowledge (p 0.003), attitude (p 0.000), motivation (p 0.020) and family support (p 0.000). On the other hand, the results of multivariate analysis showed that attitude (AOR: 6.148), family support (AOR: 2.846) and motivation (AOR: 1.912) were the dominant factors in preventing DM complications. Conclusion: Compliance with complication prevention in type 2 DM patients is the main aspect that needs to be improved through improving several factors, namely patient attitude, motivation and family support.